Feasibility of Peroral Cholangioscopy in the Initial Endoscopic Retrograde Cholangiopancreatography for Malignant Biliary Strictures - Yuichi Suzuki; Tomohiro Ishii; Haruo Miwa; Takeshi Sato; Yoshihiro Goda; Kuniyasu Irie; Kazuya Sugimori; Shin Maeda (Diagnostics)
Background: Peroral cholangioscopy (POCS) is valuable for assessing malignant biliary strictures; however, biliary drainage prior to POCS often hinders accurate diagnosis. Objectives: This retrospective study aimed to investigate the feasibility of POCS using a newly developed cholangioscope, CHF-B290, during initial endoscopic retrograde cholangiopancreatography (ERCP) for malignant biliary strictures. Methods: This multicenter retrospective study included patients who underwent initial ERCP for malignant biliary strictures at two institutions between January 2018 and March 2022. Patients who underwent initial ERCP with POCS were classified into the POCS group, and those without POCS were classified into the non-POCS group. To prevent post-POCS cholangitis, the original irrigation system for CHF-B290 was used in all POCS examinations. The primary endpoint was the rate of post-ERCP biliary infections, and the secondary endpoints were other ERCP-related complications, including pancreatitis, bleeding, and perforation. Results: Overall, 53 and 94 patients were included in the POCS and non-POCS groups, respectively. For the primary endpoint, the rate of post-ERCP biliary infection was not significantly different between the two groups (1.9% vs. 5.3%, p = 0.42). For the secondary endpoints, no significant differences were observed in the rates of post-ERCP pancreatitis (5.7% vs. 6.4%, p = 1.00) and other ERCP-related complications. The overall complication rate was 9.4% in the POCS group and 13% in the non-POCS group (p = 0.60). Conclusions: POCS during the initial ERCP for malignant biliary strictures is feasible.